Avaliação do efeito de ligantes asfálticos modificados na resistência à deformação permanente de misturas asfálticas densas - Onofre, Felipe Coutinho (2013)
Asphalt binder modification is of common use in heavy traffic roadways. Its goal is to improve binder’s rheological proper-ties, especially in extreme temperatures. The main objective of this paper was to evaluate the effect of several modified asphalt binders in dense asphalt mixes with respect to their rutting resistance and stiffness. Thirteen mixes with the same aggregate gradation and type, but with different types of polymer and polyphosphoric acid (PPA) modified asphalt binders, were investigated. Repeated load perma-nent deformation test and CDI and TDIm variables were used to evaluate the mixes’ rutting resistance. The results showed that binder modification influenced substantially the mixes rutting resistance, especially on those with polymer modified binder. In these mixes, the Flow Number, which is the failure criteria for repeated load permanent deformation test, was not reached, even after 10,000 cycles. CDI and TDIm results were mainly affected by the binder content and these results had a different ranking from the one observed in the repeated load permanent deformation test.